2017
DOI: 10.1080/19336918.2017.1322253
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal pathogens promote epithelial-mesenchymal transition in oral squamous carcinoma cells in vitro

Abstract: Epithelial-mesenchymal transition (EMT) is potentially involved in increasing metastasis of oral squamous cell carcinoma (OSCC). Periodontal pathogens are well-known for their ability to induce intense immune responses and here we investigated whether they are involved in inducing EMT. Cultures of OSCC cell line (H400) were treated separately with heat-killed periodontal pathogens F. nucleatum, or P. gingivalis or E. coli LPS for 8 d. EMT-associated features were assayed using sq-PCR and PCR-arrays, for EMT-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 48 publications
(44 reference statements)
1
82
1
1
Order By: Relevance
“…Abdulkareem et al also observed an increase of MMP2, 3 and 9, vimentin, and transcription factors, Twist and Snail, in combination with a downregulation of E‐cadherin in OSCC cells (H400 line) infected with P gingivalis . Moreover, transcriptional levels of EGF and TNF‐α were also high.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Abdulkareem et al also observed an increase of MMP2, 3 and 9, vimentin, and transcription factors, Twist and Snail, in combination with a downregulation of E‐cadherin in OSCC cells (H400 line) infected with P gingivalis . Moreover, transcriptional levels of EGF and TNF‐α were also high.…”
Section: Resultsmentioning
confidence: 89%
“…Studies were classified into three main groups according to oral specimen origins. In the first one, three studies (18.75%) used epithelial cells from human samples (Table ); in the second, three studies (18.75%) evaluated murine models (Table ); and in the last one, 11 studies (62.5%) were developed in pre‐established cell lines (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations